2023
DOI: 10.1111/jdv.19674
|View full text |Cite
|
Sign up to set email alerts
|

The causal effects of atopic dermatitis on the risk of skin cancers: A two‐sample Mendelian randomization study

Min Luo,
Yaxuan Zheng,
Qianwei Zhuo
et al.

Abstract: BackgroundObservational and epidemiological studies show conflicting results on the relationship between atopic dermatitis and skin cancer. Additionally, observational studies are susceptible to the reverse causation and confounders, thus, may not interpret true causal relationships. The causal effects of atopic dermatitis on the risk of skin cancers remains unclear.ObjectivesTo investigate the causal relationship between atopic dermatitis and skin cancer including cutaneous malignant melanoma, cutaneous squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This also led to strong methodological strengthening of Mendelian randomization and reporting of such studies making them possible in dermatology 3 . In one such study, Luo et al 4 . showed that atopic dermatitis can indeed cause cutaneous squamous cell carcinoma and basal cell carcinoma but not cutaneous malignant melanoma or actinic keratosis.…”
mentioning
confidence: 99%
“…This also led to strong methodological strengthening of Mendelian randomization and reporting of such studies making them possible in dermatology 3 . In one such study, Luo et al 4 . showed that atopic dermatitis can indeed cause cutaneous squamous cell carcinoma and basal cell carcinoma but not cutaneous malignant melanoma or actinic keratosis.…”
mentioning
confidence: 99%